Відмінкова периферія об’єктної синтаксеми в сучасній українській мові - Межов, Олександр Григорович; Mezhov, Oleksandr H. (Прикарпатський національний університет ім. В.Стефаника, 2009)
У статті проведено системне дослідження об’єктних синтаксем у зв’язку з семантичними типами предикатів. Описано відмінкові засоби вираження семантичної категорії об’єкта в елементарних та неелементарних простих реченнях. In the article the systemic investigation of the object syntaxemes in connection with semantic types of predicates was held. Сase methods of expression of the semantic category of the object in the semantically elementary and non-elementary simple sentence were described.
Features of the use of oblique cases in the secondary semantic-syntactical function of object
Keywords: синтаксема; об’єкт; предикат; відмінок; syntaxema; object; predicate; case